Jornada de horas reduzidas e equilíbrio trabalho e família no setor bancário. - Faria, Graciela Sanjutá Soares (2005)
With the changes in the work organization and the emergence of the flexible production system, especially from the 80`s, new work arrangements have appeared. One of them is the reduced hours working day in which one works a total of weekly hours smaller than the standard. Parallel to this phenomenon, the female participation in the market place has increased more noticeably from the 70`s and the conflicts between work and family have become more frequent. The reduced hours employment is pointed by some researchers as potentially favourable to the conciliation between work and family. Other researchers about the reduced hours job think it is disadvantageous to the workers because it is not their choice and it results in salary, benefit and career losses. Due to these controversies and because there isn t much research about it in Brazil, we aim to study the impact of the reduced hours work in the banks since it works with thirty-hour working day. For this reason, union trade representatives and bank workers who were employed in the countryside of São Paulo`s state were interviewed based on semi-structured outlines. Some information were collected from the RAIS (Annual List of Social Information) data base considering the period of 1994 to 2002. We found out that on the one hand the thirty-hour working day helps the bank workers to have more free time for their personal/ family activities, but most of times they don t work in this scheme by own choice and end up dealing with salary losses, less development opportunities, limited professional rise and less time to develop their activities. These aspects can limit the potential advantages of this kind of employment to the balance between work and family. We also noticed that the percentage of bank workers on thirty-hour working days in Brazil and São Paulos`s state has been decreasing and there is the predominance of women in this kind of job. Still the salary losses have been sharper for bank workers on thirty-hour working days and to the women.